Corrosion Inhibition and Acceleration by Rare Earth Ions in Galvanic Couples. Issue 16 (19th December 2019) - Oliveira, M.; Bastos, A. C.; Kallip, S.; Hack, T.; Zheludkevich, M. L.; Ferreira, M. G. S.
Abstract : Rare earth ions are amongst the most promising new generation corrosion inhibitors. This communication describes conditions where, instead of inhibition, acceleration of corrosion occurs after rare earth salts are added to solution. The work was carried out mainly with the Fe-Zn galvanic couple and different rare earth salts, using electrochemical techniques such as galvanic current measurements, scanning vibrating electrode technique and linear sweep voltammetry (polarization curves). The increased activity in the couple is associated to an unexpected cathodic reaction that is observed after adding the salts to solution. The new reaction signifies supplementary oxidant species being reduced at the iron electrode (cathode), accelerating the oxidation of zinc (anode). The nature of this cathodic process is discussed.